2022
DOI: 10.1111/1541-4337.12966
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of oleogelators in tailoring the properties of oleogels: A review

Abstract: Conventional solid fats play a crucial role as an ingredient in many processed foods. However, these fats contain a high amount of saturated fats and trans fats. Legislations and dietary recommendations related to these two types of fats set forth as a consequence of evidence showing their deleterious health impact have triggered the attempts to find alternate tailor-made lipids for these solid fats.Oleogels is considered as a novel alternative, which has reduced saturated fat and no trans fat content. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 173 publications
0
18
0
Order By: Relevance
“…It should be noted that the SA has a good gelling material due to its long aliphatic chain and the higher chain length FAs easily forms a stable gel with lower concentration (Gaudino et al ., 2019; Sivakanthan et al ., 2022). Moreover, a longer FA chain increases the melting point of oleogels and lowers the amount of gelator required for gelation (Daniel & Rajasekharan, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the SA has a good gelling material due to its long aliphatic chain and the higher chain length FAs easily forms a stable gel with lower concentration (Gaudino et al ., 2019; Sivakanthan et al ., 2022). Moreover, a longer FA chain increases the melting point of oleogels and lowers the amount of gelator required for gelation (Daniel & Rajasekharan, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, a previous comprehensive review about the utilization of EC in food applications illustrates in detail the production, structure, and properties of pure EC, as well as the mechanism of gelation and the parameters affecting the final gel properties [ 55 ]. The primary characteristic of the oleogels is that they can be developed with zero-trans and reduced saturated fats, making them a healthier lipid compared to conventional solid fats [ 56 ].…”
Section: Polysaccharide-based Edible Gels: Formulation Properties And...mentioning
confidence: 99%
“…Therefore, the lipid composition of POs can be altered to obtain the desired crystalline properties by constructing oleogels in the presence of gelators. To date, studies have focused on the effects of gelant concentration and the relative proportions of composite gels on the physicochemical properties of oleogels and on the controlled release of encapsulated fragrance components (Chen et al ., 2021; Sivakanthan et al ., 2022). Meanwhile, no systematic studies have reported on the effects of using natural oils with different melting points as base oils on oleogel gelation, textural properties, and retention of volatile components.…”
Section: Introductionmentioning
confidence: 99%